THE EFFECTIVENESS OF DIRECTED READING THINKING ACTIVITY STRATEGY IN READING COMPREHENSION OF NARRATIVE TEXT AT THE FIRST SEMESTER STAIN TULUNGAGUNG - & Akhyak, Aulia Rahman (Dinamika, 2013)
ABTRACTThis study is focused in Reading Comprehension of narrative text, because Reading is a part of language skills that needs to be increased by the students. It becomes one of the problems at the first semester of STAIN Tulungagung. It uses quantitative research with experimental research design. Here, researcher takes one group pre-test-post-test design. To know the result of experiment, the researcher uses t-test. It is because by using it, the effectiveness of teaching reading by using Directed Reading Thinking Activity can be found. Therefore, it was found that the t-value was 2.683. The result was compared with the table of t-value at 0.05 and t-value at 0.01 level of significance. Those are 1.671 and 2.392. The value was higher than t-value limit at the table of t-value, they are 1.671 < 2.392 < 2.683 . This means that the result statistically is significant.Kata Kunci: The DRTA Strategy, Reading Comprehension, Narrative Text